REPRESENTASI IDIOM BUDAYA LOKAL DALAM IKLAN ROKOK DI TELEVISI - Yayan Suherlan (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2010)
Local culture, as the cultural heritage of a nation, was originally adhered to and believed to be a set of rules and norms to be upheld in traditional community life. In a traditional community, individuals tend not to have many choices through which they can formulate their identity, and are inclined to experience difficulty in breaking free from the shackle of normative values which exist in their socio-cultural and socio-religious environment and are adhered to like a doctrine. With the onset of modernity and globalization, the values which were formally a point of reference in a traditional community become worn away until old symbols gradually become weakened and eventually replaced by new symbols provided by the global cultural market. Today, local culture is nothing more than a series of symbols which are packaged as a commodity and have a high market value. Commercial advertisements appear using local cultural idioms as a strategy for their communication. Local culture is presented through verbal and visual language with the aim of creating a positive image of the product on offer. This huge problem is the basic idea of this research. Through a case study approach, the research aims to uncover various aspects which go into the making of an advertisement, or in other words, why is an advertisement created in such an attractive way? Why is the image of an advertisement so important in building the strength of a brand name? The advertisement used as the case study for this research is a cigarette advertisement which can be seen on Indonesian television stations. The main focus of this thesis is visual communication strategy through local cultural representation. This will then show the relationship between culture, image, and the mass media as the agent which conveys the message. The research uses an interpretative method of analysis as a tool for viewing the depth of meaning of the advertisement. Keywords: local culture, advertisement, representation, television